Multidimensional Analysis of Hashtag-Driven Conversations: Detecting Hybrid Discourse Patterns in the #KaburAjaDulu Twitter Campaign - Andri Fauzan Adziima; Wahyu SJ Saputra; Windri Saifudin; Meisya Vira Amelia; Alumdadini Bilqis Lanisari (Universitas Pendidikan Ganesha, 2026)
This study investigated the multidimensional dynamics of the Indonesian hashtag #KaburAjaDulu on Twitter (X) between April and July 2025. By integrating sentiment analysis, social network analysis (SNA), and topic modeling, the research developed a framework to distinguish organic grassroots discourse from coordinated non-organic amplification, often associated with